2012
DOI: 10.1088/0957-4484/23/45/455302
|View full text |Cite
|
Sign up to set email alerts
|

Formation of oriented nanostructures in diamond using metallic nanoparticles

Abstract: A simple, fast and cost-effective etching technique to create oriented nanostructures such as pyramidal and cylindrical shaped nanopores in diamond membranes by self-assembled metallic nanoparticles is proposed. In this process, a diamond film is annealed with thin metallic layers in a hydrogen atmosphere. Carbon from the diamond surface is dissolved into nanoparticles generated from the metal film, then evacuated in the form of hydrocarbons and, consequently, the nanoparticles enter the crystal volume. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…The natural alignment along the [110] and [–110] crystallographic directions of the nickel‐etched microstructures shown in Figure can also be observed in the works of Smirnov et al and Mehedi et al The borders of the microstructures are found to be parallel to the [110] and [–110] directions (Figure b). The mean diagonal size of the microstructures was determined from the measurement of 112 microstructures, yielding a value of 491 ± 219 nm.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The natural alignment along the [110] and [–110] crystallographic directions of the nickel‐etched microstructures shown in Figure can also be observed in the works of Smirnov et al and Mehedi et al The borders of the microstructures are found to be parallel to the [110] and [–110] directions (Figure b). The mean diagonal size of the microstructures was determined from the measurement of 112 microstructures, yielding a value of 491 ± 219 nm.…”
Section: Resultssupporting
confidence: 74%
“…Another kind of microstructuring is possible to locally obtain (111) oriented surfaces on the main (100) diamond orientation. Smirnov et al and Mehedi et al have shown that the deposition of a thin nickel film followed by annealing at about 900°C in a hydrogen atmosphere caused the dewetting of the nickel layer into nickel particles, and the catalytic etching of diamond until the formation of inversed pyramidal shaped holes.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction at the nickel/diamond interface is a key question in a variety of applications, such as epitaxial growth of diamond lms on nickel substrates, 1,2 catalytic etching of diamond surfaces, [3][4][5][6][7][8] and the design of diamond-metal composites with nickel-containing binders. [9][10][11] It is also of great interest from the fundamental point of view as the processes occurring at the nickel/diamond interface exemplify the interaction between two phases, one of which is metastable.…”
Section: Introductionmentioning
confidence: 99%
“…However, such structures need an accurate control of lateral growth or lateral etching to guarantee the best epitaxial growth, with a well‐faceted surface and the minimum number of emerging defects. These material constraints are expected to limit the current leakage and to increase the breakdown voltage in the future devices .…”
Section: Introductionmentioning
confidence: 99%